The hybrid systems method integrating human factors analysis and classification system and grey relational analysis for the analysis of major coal mining accidents. (12th December 2018) - Feng, Yan; Chen, Hong; Zhang, Yingyu; Jing, Linlin
Abstract : The coal mine safety situation remains grim in China. This study proposed a hybrid systems method integrating the human factors analysis and classification system and grey relational analysis to determine the key factors causing coal mine casualties. The method was applied to analyse 94 coal mining accidents from 1997 to 2011, and the results were as follows. (a) Among the five levels, "unsafe acts" has the highest grey relational grade with accident casualties, followed by "preconditions for unsafe acts, " "organizational influences, " "unsafe supervision, " and "external factors." (b) Among all categories, "inadequate supervision" has the closest relationship with accident casualties, followed by "violations, " "environmental factors, " and "errors." (c) "Naked fire in flammable and explosive places" and "untimely accident handling or improper handling measures" are important indicators affecting accident casualties. Finally, some corresponding suggestions for safe coal mine production were proposed.